The significance of corporate social responsibility disclosure to Islamic banks in Malaysia: an Islamic view - Wan Jusoh, Wan Noor Hazlina; Ibrahim, Uzaimah (IIUM Institute of Islamic Banking and Finance (IIiBF), International Islamic University Malaysia (IIUM)., 2018)
Corporate social responsibility disclosure (CSRD) is imperative for an institution as it assists decision makers in making economic decisions. However, for Islamic institutions like Islamic banks, these objectives are secondary. For Islamic banks, to show their compliance with Shari’ah is the main objective of their CSRD that overrules other objectives. Nevertheless, there is no special framework on corporate social responsibility (CSR) for Islamic financial institutions in Malaysia especially Islamic banks thus far to guide them on what should be disclosed in their annual reports although Malaysia is one of the leading global hub for Islamic finance. Hence, the purpose of this study is to determine the significance of CSRD to Islamic banks in Malaysia from an Islamic view. This study is based on primary Shari’ah sources i.e. al-Qur’an and al-Sunnah, and secondary Shari’ah sources. It was found that, it is obligatory for all Islamic banks in Malaysia to disclose their CSR activities and initiatives through a right and common platform, which is CSRD. Therefore, a special CSR framework is required to guide Islamic banks in Malaysia disclose their CSR activities or initiatives systematically and perfectly